Pengetahuan Ibu Tentang Materi Perawatan Masa Nifas Dalam Buku Kia Dengan Keteraturan Kunjungan Nifas - Ika Yudianti; Ari Kusmiwiyati; Puji Rahayu (Jurnal Kebidanan dan Kesehatan Tradisional, 2017)
Abstract : Maternal And Child Health-Book, Women's Knowledge, Postnatal Visit. In 2015, the national coverage of postnatal visit only reached 87.06% of the target 95%. The mother’s and child’s health book (MCH book) contains comprehensive medical records and information, including postpartum care. If the KIA's book material is read and understood by the mother, her knowledge will increasing, so we can expect her to be willing to do the postpartum visit according to the government’s program. This research aimed to learn about the correlation between postnatal woman’s knowledge on postnatal services and her postnatal visit regularity. Design used was correlational study with cross sectional approach. The population was all post-natal women who have MCH book at a private midwife practice in May - June 2017 of total 35 women. Samples taken by simple random technique. Data collection tool used was questionnaire and MCH book. The result showed that a small amount of respondents with good knowledge about postnatal care (28,1%) done postpartum visit in accordance with the government’s program. Women with less knowledge level (18,8%), few of them (3.1%) made postnatal visits in accordance with the program. Chi-square analysis obtained ρ value (0.001) that means less than a (0,05), so the null hypothesis rejected. Hence, there was correlation between postnatal woman’s knowledge on postnatal services and her postnatal visit regularity. The results of the study said that most of the well-informed women about postnatal services will do postpartum visits according to government programs. Postpartum women need to be motivated to read postpartum care materials in maternal and child health-book.